A Comparison of Tumor Biology in Primary Ductal Carcinoma In Situ Recurring as Invasive Carcinoma versus a New In Situ. (29th December 2013) - Zhou, Wenjing; Johansson, Christine; Jirström, Karin; Ringberg, Anita; Blomqvist, Carl; Amini, Rose-Marie; Fjallskog, Marie-Louise; Wärnberg, Fredrik
Abstract : Introduction . About half of all new ipsilateral events after a primary ductal carcinoma in situ (DCIS) are invasive carcinoma. We studied tumor markers in the primary DCIS in relation to type of event (invasive versus in situ ). Methods . Two hundred and sixty-six women with a primary DCIS from two source populations, all with a known ipsilateral event, were included. All new events were regarded as recurrences. Patient and primary tumor characteristics (estrogen receptor (ER), progesterone receptor (PR), HER2, EGFR, and Ki67) were evaluated. Logistic regression was used to calculate odd ratios and 95% confidence intervals in univariate and multivariate analyses. Results . One hundred and thirty-six of the recurrences were invasive carcinoma and 130 were in situ . The recurrence was more often invasive if the primary DCIS was ER+ (OR 2.5, 95% CI 1.2–5.1). Primary DCIS being HER2+ (OR 0.5, 95% CI 0.3–0.9), EGFR+ (OR 0.4, 95% CI 0.2–0.9), and ER95−/HER2+ (OR 0.2, 95% CI 0.1–0.6) had a lower risk of a recurrence being invasive. Conclusions . In this study, comparing type of recurrence after a DCIS showed that the ER−/HER2+ tumors were related to a recurrence being a new DCIS. And surprisingly, tumors being ER+, HER2−, and EGFR− were related to a recurrence being invasive cancer.